A critical review on the assurance of accuracy in automated complete blood count test reports by rectification of spuriously elevated MCHC values - Saidarakath, Jazeera; Bery, Kaumudi; Ahmed, Issameldin Abdelmoniem Elsamani; Ambra, Hanan (International Journal of Research in Medical Sciences, 2025)
Spuriously elevated or decreased results are encountered frequently in hematology analysers in various parameters of the complete blood count (CBC). These results can be either true reflections of patient’s disease or may be spurious findings due to multiple pre- analytical factors. It is necessary to review these spurious results and perform necessary corrective actions before issuing the final report to the patient. Correction of spurious results ensures accuracy of the patient results and thereby helps the clinicians in providing optimal diagnosis and treatment to the patients. In this study, the predominant focus is on mean corpuscular haemoglobin concentration (MCHC) elevation which is derived as a calculation from haemoglobin and haematocrit values. As a result, it can be affected by preanalytical, postanalytical or analytical factors. In literature there are only a few articles related to correction of spuriously high MCHC. This article reviews most important studies available in literature on correction of spuriously high MCHC.